Salvianolic acid A facilitates cartilage repair in knee osteoarthritis model rats by promoting WDR5 expression - Hua He; Dali Dong (Regenerative Therapy)
Background: The aim of this study was to investigate the regulation of Salvianolic acid A (SAA) on the chondrogenic differentiation of bone mesenchymal stem cells (BMSCs), and its effect on cartilage repair in knee osteoarthritis (KOA) model rats and the action mechanism. Methods: Immunohistochemistry was performed to detect collagen type II (COL2A1), MMP13 and caspase-3 (CASP3) expression in cartilage tissues, and Safranin-O/Fast Green staining for cartilage damage. Alcian blue staining was performed to measure chondrogenic differentiation of BMSCs. Chondrocyte apoptosis was detected by using flow cytometry. Results: SAA treatment significantly attenuated cartilage damage in KOA model rats in a dose-dependent manner, and inhibited chondrocyte apoptosis induced by IL-1β in a dose-dependent manner. Moreover, SAA treatment promoted chondrogenesis-related proteins (COL2A1 and Aggrecan) expression and inhibited catabolism-related proteins (MMP13 and MMP3) expression both in the cartilage tissues from KOA model rat and in the IL-1β-treated chondrocytes. WD repeat domain 5 (WDR5) was a downstream target of SAA, and it facilitated chondrogenic differentiation of BMSCs derived from KOA model rats (KOA-BMSCs). Importantly, the inhibition of SAA treatment to the apoptosis and catabolism of chondrocyte and the promotion of SAA treatment to chondrogenic differentiation of KOA-BMSCs were rescued by silencing WDR5. Conclusion: Overall, SAA treatment could facilitate cartilage repair via inhibiting the apoptosis and catabolism of chondrocyte and promoting chondrogenic differentiation of KOA-BMSCs by promoting WDR5 expression. Our data suggested that SAA may a potential drug for the treatment of KOA.